Water quality of Narai canal and Balu river of Dhaka City: An impact of industrialization (Journal of the Bangladesh Agricultural University, 2016)
Rapid industrialization around riverside without having proper environmental consideration causes severe water pollution in our country. On accordance with the consecution of this problem the study was conducted to investigate the water quality of Narai canal and Balu river during January to June, 2012. Water quality parameter analysis i.e. color, odor, pH, total dissolved solids (TDS), dissolved oxygen (DO), ammonium (NH4) results show that except pH all exceeded standard limit for domestic water use, irrigation and fish cultivation. The minimum and maximum values of pH, TDS, DO and NH4 were 6.89-7.33, 982-1308 ppm, 0.33-2.12 ppm and 6.79-89.76 ppm, respectively. Present analysis with secondary research data also revealed that this pollution rate is becoming intensified quickly which may pose a great threat in future for human health, ecosystem and sustainable agricultural production. So, Effluent Treatment Plants (ETP) is urgently needed to minimize the concentration of pollutants and ultimately to save the river water of the concerned area.J. Bangladesh Agril. Univ. 12(2): 285-290, December 2014